(untitled) (Journal of the Bangladesh Agricultural University, 2020)
The study was carried out to observe the formation of urban heat island (UHI) under different land use patterns (built-up area, vegetated area, water body and bare soil) in Mymensingh city. Temperature and relative humidity of 30 years (1987-2016) were collected from Bangladesh Meteorological Department. Air temperature and relative humidity were measured at three hours interval on 18 July, 10 August and 10 September, 2017 over selected locations of Mymensingh city and of its suburban rural area (Phulpur upazila) using Thermo-hygro data logger to investigate the heat island phenomena and heat stress condition. During the period of 1987-2016, annual average temperature increased by 0.0094 °C/year in Mymensingh city. In comparison with the rate of temperature increase in its suburban rural area, the rate of increase in Mymensingh city was higher indicating the existence of urban heat island in this city. In Mymensingh city, the highest (38.5 °C) temperature was found in built-up area in July and the lowest (27 °C) was found in water body in August. In Phulpur, temperature was also highest in July with the maximum of 35.8 °C and lowest in August (35 °C). Temperature was higher both in day and night in Mymensingh city compared to Phulpur rural area, signalling the urban warming phenomenon (UHI) in Mymensingh city. In Mymensingh, maximum urban heat island intensity (UHII) was 5.2 °C in July and minimum was 0.6 °C in September. UHII was higher at midnight and after that it gradually decreased. Thermo hygrometric index (THI) ranged from 28.8 °C to 32.1°C for Mymensingh city and 25.7 °C to 31.5 ° C for Phulpur rural area indicates the more comfortable condition in Phulpur rural area. The study revealed that increased imperviousness in urban area increased the urban heat island phenomena compare to its surrounding suburban rural area. J Bangladesh Agril Univ 18(2): 347–353, 2020 https://doi.org/10.5455/JBAU.76524